Consideration of appropriate clinical applications for cardiac xenotransplantation. Issue 8 (29th June 2018) - Chan, Joshua L.; Miller, Justin G.; Singh, Avneesh K.; Horvath, Keith A.; Corcoran, Philip C.; Mohiuddin, Muhammad M.
Abstract: The field of cardiac xenotransplantation has entered an exciting era due to recent advances in the field. Although several hurdles remain, the use of rapidly evolving transgenic technology has the potential to address current allogeneic donor pool constraints and mechanical circulatory system device limitations. The success of xenotransplantation will undoubtedly be dependent on specific patient selection criteria. Defining these particular indications for xenotransplantation is important as we approach the possibility of clinical applications.